IDENTIFIKASI UNSUR-UNSUR KEPOPULERAN SERIAL TV DRAMA KINPACHI SENSEI DAN TRANSFORMASINYA BERDASARKAN TEORI FORMULA - Santi Andayani (Universitas Diponegoro, 2013)
ABSTRACT The paper describes theidentification ofthe elements of popularity TV drama seriesKinpachi Senseiand its transformationbased on thetheoryformulawithapproachesthat examinecontinuity, repetition, duplicationandimitationofa formand elements ofpopularfiction. In addition, thesyntacticsemanticapproaches and qualitativeapproachto collect datain the form ofwrittendocuments such as quotationsandstatistics will use too. The result of this study concludes that history of a work to be popular can not be separated from the influence of society culture in the coloring of a genre. Key words: popular culture, formula, convention, school life, TV drama.